Self-rated health among Greenlandic Inuit and Norwegian Sami adolescents: associated risk and protective correlates - Anna Rita Spein (International Journal of Circumpolar Health, 2013)
Objectives. Self-rated health (SRH) and associated risk and protective correlates were investigated among two indigenous adolescent populations, Greenlandic Inuit and Norwegian Sami. Design. Cross-sectional data were collected from “Well-being among Youth in Greenland” (WBYG) and “The Norwegian Arctic Adolescent Health Study” (NAAHS), conducted during 2003–2005 and comprising 10th and 11th graders, 378 Inuit and 350 Sami. Methods. SRH was assessed by one single item, using a 4-point and 5-point scale for NAAHS and WBYG, respectively. Logistic regressions were performed separately for each indigenous group using a dichotomous measure with “very good” (NAAHS) and “very good/good” (WBYG) as reference categories. We simultaneously controlled for various socio-demographics, risk correlates (drinking, smoking, violence and suicidal behaviour) and protective correlates (physical activity, well-being in school, number of close friends and adolescent–parent relationship). Results. A majority of both Inuit (62%) and Sami (89%) youth reported “good” or “very good” SRH. The proportion of “poor/fair/not so good” SRH was three times higher among Inuit than Sami (38% vs. 11%, p≤0.001). Significantly more Inuit females than males reported “poor/fair” SRH (44% vs. 29%, p≤0.05), while no gender differences occurred among Sami (12% vs. 9%, p≤0.08). In both indigenous groups, suicidal thoughts (risk) and physical activity (protective) were associated with poor and good SRH, respectively. Conclusions. In accordance with other studies of indigenous adolescents, suicidal thoughts were strongly associated with poorer SRH among Sami and Inuit. The Inuit–Sami differences in SRH could partly be due to higher “risk” and lower “protective” correlates among Inuit than Sami. The positive impact of physical activity on SRH needs to be targeted in future intervention programs.